Índice de área foliar, coeficiente de cultura e produtividade de cafeeiro fertirrigado - Sant'Ana, José Antonio do Vale (2015)
This study aimed at monitoring the time evolution of coffee plant leaf area index; of coffee plant single crop coefficient (Kc); of average coffee bean yield evolution; and of NO3- and K+ ions concentration at the saturated soil extract on irrigated coffee plantations subjected to different splitting applications strategies of different nitrogen and potassium fertilization rates. Five application rates (30%, 80%, 130%, 180% and 230% of the recommended amount of N and K2O for non-irrigated coffee plants growing in the Minas Gerais region), and two splitting application strategies (four applications on Nov, Dec, Jan and Feb, and 12 monthly applications) were evaluated. The experiment was conducted at an experimental area of the Universidade Federal de Lavras, in Lavras, Minas Gerais, where coffee plants, Catiguá MG-3 cv, were transplanted on May 2007, in a 2.5 x 0.6 meters spacing. Livestock urea (45% N) and potassium nitrate (13% N and 44% K2O) were used as sources of N and K2O. The Logistic and Gompertz models showed good adjustments on describing the time evolution of coffee leaf area index. The time evolution of coffee plant leaf area index and the time evolution of average coffee bean yield, for the 2010, 2011, 2012, and 2013 harvests, were not affected by the two evaluated splitting application strategies. The relationship among average coffee bean yield and nitrogen and potassium fertilizer rates was best described by the Mistcherlich model. Restrictions on both coffee plants growth and coffee bean yield were observed on the plots receiving potassium and nitrogen fertilizer rates lower than 80% of the recommended amount. The single crop coefficient for the drip irrigated Catiguá MG-3 cv. coffee plots ranged from a minimum value of 0.21 to a maximum value of 0.80, with an average Kc value of 0.57. In a general way, the time evolution of NO3- and K+ ions concentration in the saturated soil extract showed a high variability in time, although, under the 12 monthly applications splitting application strategy a greater temporal stability was observed. Higher levels of NO3- and K+ leaching were observed on the plots receiving only four applications of nitrogen and potassium fertilizers.